Faktor-Faktor Yang Mempengaruhi Konsumen Dalam Keputusan Pembelian Unggas di Pasar Depok Surakarta - Wijaya, Jonet Raka Ady; Kusasih, Ida Ayu K. R.; Mutmainah, Hestin (STIE Surakarta, 2014)
Depok market known as birds, especially poultry market and become one of theÂ reference point to search for orbuy poultry. Many things affect consumer purchasing decisions. The purpose of this study is the extent of quality, price, and location influence the purchasing decisions of poultry. The sample used in this study is that consumers in the Depok market as much as 97 respondents. The analysis tool used Is a test instrument that includes validity and reliability test while hypothesis testing using multiple linear regression test, t test, F test and coefficient of determination. Based on the results of analysis show that the variable quality, price, and location has a significant effect partially or simultaneously to the purchasing decision, the price variable has the most dominan tinfluence on purchasing decisions